Estudos de usuários da informação: tipificando os usuários internos e externos do arquivo central do Instituto Federal da Paraíba (IFPB) João Pessoa/PB - Leite, Mayara Machado (2017)
The studies directed to the users of the information need more investigations, mainly, the users of the archival information, therefore, the main goal of the research was to typify the internal and external users of the Central Archive of the Coordination of Academic Control (CCA) of the Federal Institute of Paraíba (IFPB) and how to identify the profile of internal and external users, identify users' needs, search and use according to the phenomenology and analyze the metacognition in the process of informational behavior of users. The theoretical framework uses Capurro (2003), Araújo (2008), Ávila e Sousa (2011) and Dervin (1983). From the methodological point of view, this is a qualitative, quantitative and exploratory research that uses the theoretical bases in phenomenological studies, participatory observation and semi-structured interview that has a cut of the universe studied with 300 users between the Current and Intermediate Archive in which were analyzed in five stages outlined as Profile, Need, Behavior, Search and Use of information. It is possible to affirm that the research made possible a contributory coverage for new theoretical and practical perspectives in the studies of users of the archival information, from the foundations found, it is concluded that the users are beyond the passive conditions that the archives offer and that their classifications can be diversified according to the demand of the Archive, however, the research clarified a focus on the development of users in the technological aspect, in order to reach new terminologies regarding the classification of archival users, thus emphasizing guidelines in Archives and Information Science , it is expected that the results will lead to the development of new research